SAT0189 Rapid Onset of Clinical Benefit in Patients with RA Treated with Mavrilimumab, A Fully Human Monoclonal Antibody Targeting GM–CSFR-ALPHA: Subanalysis of the Phase IIB Earth Explorer 1 Study. (9th June 2015) - McInnes, I.B.; Burmester, G.R.; Kremer, J.M.; Miranda, P.; Korkosz, M.; Vencovsky, J.; Rubbert-Roth, A.; Mysler, E.; Close, D.; Sleeman, M.; Godwood, A.; Albulescu, M.; et al.
Abstract : Background: Macrophages are pivotal to the pathogenesis of rheumatoid arthritis (RA), and their inflammatory products drive many of the signs and symptoms of disease. Mavrilimumab inhibits macrophage activation and survival via blockade of granulocyte-macrophage colony-stimulating factor receptor-α (GM–CSFR-α) and has demonstrated sustained clinical benefit in patients with RA. 1 Objectives: To examine time to onset of clinical response to mavrilimumab in the EARTH EXPLORER 1 study. Methods: In a 24-week, Phase IIb study (NCT01706926 ), patients with adult-onset RA (18–80 years; Disease Activity Score 28 C-reactive protein [DAS28–CRP] >3.2; ≥4 swollen joints; inadequate response to ≥1 disease-modifying antirheumatic drugs [DMARDs]) receiving concomitant methotrexate were enrolled. Patients received mavrilimumab (150, 100, or 30 mg every other week [eow]) or placebo, administered subcutaneously with methotrexate (7.5–25.0 mg/week). Efficacy assessments included DAS28–CRP, American College of Rheumatology (ACR)20/50/70 responses, CRP, erythrocyte sedimentation rate (ESR), swollen joint count (SJC), tender joint count (TJC), and pain assessments. Results: 326 patients with mean (SD) DAS28–CRP 5.8 (0.9) were randomized to mavrilimumab (150, 100, or 30 mg eow) or placebo (N=79, 85, 81, and 81, respectively). At Week 1 (first assessment), all mavrilimumab dosages demonstrated significant reductions from baseline in DAS28–CRP ( p <0.001 vs. placebo), with treatment benefit increasing through Week 12. Significant improvements for mavrilimumab 150 mg eow vs. placebo were demonstrated at Week 1 for CRP, ESR, SJC, TJC, and pain ( p =0.003 to p <0.001; Table ). Effects of mavrilimumab 150 mg eow were near maximum compared with placebo for CRP, ESR, and pain at Week 1, and were sustained until Week 24. SJC and TJC for mavrilimumab 150 mg eow improved from baseline to Week 1, and continued to improve through Week 12. This improvement was sustained through Week 24. Conclusions: By targeting activated macrophages via inhibition of GM–CSFR-α, mavrilimumab substantially reduced patients' RA disease activity early in their treatment, from first dose (Week 1) to final assessment for many patients, as evaluated by several clinical outcomes. References: Burmester GR, et al. Ann Rheum Dis. 2013;72:1445–52. Acknowledgements: Funded: MedImmune Ltd. Editorial assistance: N Panagiotaki, QXV Communications, UK Disclosure of Interest: I. McInnes Grant/research support from: MedImmune (Research award to University of Glasgow), Consultant for: MedImmune, AstraZeneca, G. Burmester Grant/research support from: AbbVie, Pfizer, UCB, Roche, Consultant for: AbbVie, BMS, Novartis, MedImmune, MSD, Pfizer, UCB, Roche, Speakers bureau: AbbVie, BMS, Novartis, MSD, Pfizer, UCB, Roche, J. Kremer Shareholder of: Corrona, Grant/research support from: AbbVie, Amgen, Genentech, Lilly, Pfizer, Consultant for: AbbVie, Amgen, Genentech, Lilly, Pfizer, BMS, Employee of: Corrona, P. Miranda Grant/research support from: MedImmune (to support protocol), M. Korkosz: None declared, J. Vencovsky: None declared, A. Rubbert-Roth Grant/research support from: Pfizer, Chugai, Consultant for: MSD, UCB, Abbott, Pfizer, Roche, BMS, Chugai, Speakers bureau: Roche, Pfizer, UCB, E. Mysler Grant/research support from: MedImmune, Roche, BMS, Pfizer, D. Close Shareholder of: AstraZeneca, Employee of: MedImmune, M. Sleeman Shareholder of: AstraZeneca, Employee of: MedImmune, A. Godwood Shareholder of: AstraZeneca, Employee of: MedImmune, M. Albulescu Employee of: MedImmune, M. Weinblatt Grant/research support from: BMS, UCB, Crescendo Bioscience, Consultant for: MedImmune, AstraZeneca, Amgen, Abbvie, BMS, Crescendo bioscience, Lilly, Pfizer, UCB, Roche